The Interpretation of a New Generation of Persian So-called Friendship Humors According to Grecian Principles of Co-operation - Sadighe Sadat Meghdari; Zahra Ezaddosost (مطالعات زبانی و بلاغی)
In this study, we have tried to interpret a new generation of so-called friendship humors according to Grecian principles of co-operation in Persian language. Reviewing the implications of utterances and their meanings in context is one of the most important aspects of language usage. In fact, people do not always suggest explicitly what they are meant, and this can be lead to an unsuccessful mutual interacting. Grecian co-operative principles (1975) can be one of the most important factors in creating a successful Humor. This study aims to investigate the violations of Grecian co-operative principles and their role in the joke production of the kind that is just widespread in the Persian language in everyday conversations. The field research is descriptive-analytic. The data include 30 jokes, internet dialogues and messages that are randomly selected. The results showed that the consequences of violation of Grecian co-operation principles results in lying, idiom, ridicule, metaphor, hyperbole, secrecy, emphasizing the subject, insults, lack of desire to continue the discussion, ambiguity, contradiction, surprised the audience, change topic in the Persian-speaking community.